Effect of Maize (Zea mays) and Soybean (Glycine max) Cropping Systems on Weed Infestation and Resource Use Efficiency - Aamir Ali; Shoaib Ahmed; Ghulam Mustafa Laghari; Abdul Hafeez Laghari; Aijaz Ahmed Soomro; Nida Jabeen (Agronomy)
Agriculture has consistently improved to meet the needs of a growing global population; however, traditional monoculture farming, while highly productive, is facing challenges such as weed infestation and inefficient resource utilization. Herbicides effectively control weeds. However, their widespread use in weed management has the potential to contaminate soil and water, endangering the ecosystem by damaging non-target plant and animal species. Therefore, the main objective of this study was to evaluate the impact of different maize and soybean cropping systems on weed infestation and resource utilization. The experiment was a randomized complete block design with three replications consisting of three cropping systems: sole maize (SM), sole soybean (SS), and maize–soybean strip intercropping (MSI). In this study, the main difference between SM, SS, and MSI was the planting density, which was 60,000 (SM), 100,000 (SS), and 160,000 (maize–soybean in MSI). We observed that a higher total leaf area index in MSI resulted in increased soil cover, which reduced the solar radiations for weeds and suppressed the weed growth by 17% and 11% as compared to SS and SM, respectively. Whereas the radiation use efficiency for companion crops in MSI was increased by 39% and 42% compared to SS and SM, respectively. Moreover, the increased soil cover by total leaf area index in MSI also increased the efficiency of water use. Furthermore, our results indicated that reduced weed-crop competition increased the resource use in MSI, which resulted in increased crop yield and land equivalent ratio (LER 1.6). Eventually, this resulted in reduced inputs and increased land productivity. Therefore, we suggest that MSI should be adopted in resource-limiting conditions with higher weed infestation as it can simultaneously promote ecological balance and improve agricultural output, thereby reducing the environmental effects of traditional cropping systems.